2019
DOI: 10.1007/s40279-019-01193-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pregnancy Physical Activity with Maternal Cardiometabolic Health, Neonatal Delivery Outcomes and Body Composition in a Biethnic Cohort of 7305 Mother–Child Pairs: The Born in Bradford Study

Abstract: Objective Physical activity is advocated for a range of benefits to the uncomplicated pregnancy. We investigated associations of mid-pregnancy physical activity with maternal and neonatal health in white British and Pakistani-origin women from a deprived urban setting. Methods The study was performed in 6921 pregnant women (53% Pakistani-origin) who contributed data for 7305 singleton births. At 26-28 weeks gestation, women were grouped into four activity levels (inactive/somewhat active/moderately active/ act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 52 publications
1
42
0
1
Order By: Relevance
“…Maternal age at delivery was calculated as the time elapsed between the mother and child's dates of birth and was collapsed to three categories (< 25y, 25 to < 30y, ≥30y). Children who were part of the Born in Bradford birth cohort study were matched to birth weight using NHS patient identifiers [23]. Birth weight was categorised as low (< 2500 g), normal (2500 to 3500 g), or high (> 3500 g) [24].…”
Section: Independent Variables: Socio-demographic Temporal and Perinmentioning
confidence: 99%
“…Maternal age at delivery was calculated as the time elapsed between the mother and child's dates of birth and was collapsed to three categories (< 25y, 25 to < 30y, ≥30y). Children who were part of the Born in Bradford birth cohort study were matched to birth weight using NHS patient identifiers [23]. Birth weight was categorised as low (< 2500 g), normal (2500 to 3500 g), or high (> 3500 g) [24].…”
Section: Independent Variables: Socio-demographic Temporal and Perinmentioning
confidence: 99%
“…Maternal physical activity was assessed at 26-28 weeks gestation using the General Practice Physical Activity Questionnaire (GPPAQ) which has been validated against accelerometry and exhibits face validity in the BiB pregnancy cohort (National Health Service, 2009;Collings et al, 2020aCollings et al, , 2020b. Mothers were grouped into one of four activity levels (inactive/somewhat active/moderately active/active) based on their self-reported occupational physical activity level, physical exercise and walking.…”
Section: Methodsmentioning
confidence: 99%
“…Women consented to the abstraction and use of their data from obstetric medical records and at recruitment completed an interviewer administered questionnaire. Full details of all covariables have previously been described (Collings et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the benefits of PA participation during pregnancy. These include reduced risk of excessive gestational weight gain [ 14 , 15 , 16 , 17 ] and of developing conditions such as gestational diabetes mellitus (GDM) [ 15 , 18 , 19 , 20 ], pre-eclampsia [ 15 , 20 , 21 , 22 ], lower levels of maternal pregnancy triglycerides and a higher concentration of high-density lipoprotein cholesterol (HDL-c), [ 23 ] and neonatal cord blood HDL-c levels [ 24 ]. Lower rates of preterm birth [ 25 , 26 , 27 ], miscarriage [ 28 ], reduced length of labour, lowered risk of caesarean delivery and complications [ 21 , 25 , 27 , 29 , 30 ], reduced risk of macrosomia [ 28 , 31 ] and reduced risk of low birth weight [ 25 ] are also counted as benefits.…”
Section: Introductionmentioning
confidence: 99%